Feasibility study of a minibeam collimator design for a 60Co gamma irradiator - Moradi, F.; Khandaker, Mayeen Uddin *; Abdul Sani, S.F.; Uguru, E.H.; Sulieman, A.; Bradley, D.A. * (Elsevier, 2021)
Recently much attention has been paid to microbeam and minibeam irradiations, present interest focusing on their use in study of the behaviour of single cells, groups of cells, also their application in spatially fractionated radiotherapy. Synchrotrons are the most common source for microbeam radiotherapy (MRT), albeit limited in access and typically offering photon energies very much lower than familiar in the practice of conventional radiotherapy. In this study of feasibility, the design has been investigated of a collimator coupled to a conventional 60Co gamma-irradiator sample chamber to produce a minibeam. MCNPX code Monte Carlo simulations were used to model a Gammacell 220 60Co irradiator with lead and tungsten collimators. The dose profile was evaluated in the absence and presence of the collimator, seeking to optimize collimator design. The results pertain to specific shapes of lead and tungsten collimators producing narrow (millimeter dimension) beams, sufficient in thickness but yet still fitting within the sample chamber, with a peak-to-valley dose ratio (PVDR) greater than 15. The beam size can be tailored with modification in the size of the perforated part, the collimator optimized to minimize the dose-rate at points away from the collimator centre. However the dose-rate at the centre is reduced to between 2 to 20% of that in the absence of collimator. The findings of this study encourage the development of minibeam collimator for gamma irradiators, useful for preclinical minibeam radiotherapy research in centres with little or no access to other appropriate sources.